Mannitol transport and mannitol dehydrogenase activities are coordinated in olea europaea under salt and osmotic stresses - Conde, Artur (2011)
This is a pre-copy-editing, author-produced PDF of an article accepted for publication in Plant and Cell Physiology following peer review. The definitive publisher-authenticated version is available online at http://pcp.oxfordjournals.org/cgi/content/abstract/pcr121? ijkey=6orgUM5fkIjedYn&keytype=ref